Clinicopathological and prognostic significance of NM23 expression in patients with non-small cell lung cancer: A systematic review and meta-analysis. Issue 47 (24th November 2021) - Min, Shi-hui; Zheng, Qiang-qiang
Abstract: Background: There is a heated debate on the clinicopathological features and prognostic significance with non-metastasis 23 (NM23) expression in patients with non-small cell lung cancer (NSCLC). Thus, we conducted this meta-analysis to evaluate the clinicopathological features and prognostic significance of NM23 for NSCLC patients. Methods: Pubmed, Embase, and Web of Science were exhaustively searched to identify relevant studies published prior to March, 2020. Odds radios (ORs) and hazard radios with 95% confidence intervals (CIs) were calculated to summarize the statistics of clinicopathological and prognostic assessments. Q-test and I 2 -statistic were utilized to assess heterogeneity across the included studies. We also performed subgroup analyses and meta-regression analyses to identify the source of heterogeneity. Publication bias was detected by Begg and Egger tests. Sensitivity analysis was used to value the stability of our results. All the data were analyzed using statistical packages implemented in R version 4.0.5. Results: Data from a total of 3170 patients from 36 studies were extracted. The meta-analysis revealed that low expression of NM23 was correlated with higher risk of NSCLC (OR = 4.35; 95% CI: 2.76–6.85; P  < .01), poorer tumor node metastasis (TNM) staging (OR = 1.39; 95% CI: 1.01–1.90; P  = .04), poorer differentiation degree (OR = 1.37; 95% CI: 1.01–1.86; P  = .04), positive lymph node metastasis (OR = 1.83; 95% CI: 1.22–2.74; P  < .01), lung adenocarcinoma (OR = 1.45; 95% CI: 1.20–1.75; P  < .01), and poorer 5-year overall survival (OS) rate (hazard radio = 2.33; 95%CI: 1.32–4.11; P  < .01). The subgroup analyses and meta-regression analyses suggested that the "Publication year", "Country", "Sample size", and "Cutoff value" might be the source of heterogeneity in TNM staging, differentiation degree, and lymph node metastasis. Both Begg test and Egger test verified that there were publication bias in 5-year OS rate. Sensitivity analysis supported the credibility of the results. Conclusion: The reduced NM23 expression is strongly associated with higher risk of NSCLC, higher TNM staging, poorer differentiation degree, positive lymph node metastasis, lung adenocarcinoma, and poorer 5-year OS rate in NSCLC patients, which indicated that NM23 could serve as a biomarker predicating the clinicopathological and prognostic significance of NSCLC.